Switchable Perovskite Photovoltaic Sensors for Bioinspired Adaptive Machine Vision. (21st September 2020) - Chen, Qilai; Zhang, Ying; Liu, Shuzhi; Han, Tingting; Chen, Xinhui; Xu, Yanqing; Meng, Ziqi; Zhang, Guanglei; Zheng, Xuejun; Zhao, Jinjin; Cao, Guozhong; Liu, Gang
Abstract : Adaptive Machine Vision In article number 2000122, Jinjin Zhao, Guozhong Cao, and Gang Liu design a bioinspired smart machine vision system. Benefiting from the switchable photovoltaic characteristics of the perovskite‐based sensor devices, high‐fidelity adaptive image sensing and neuromorphic processing of the optical information is made possible with the sensory neural network, offering new and highly efficient computation paradigm for post‐Moore era.